2019
DOI: 10.18343/jipi.24.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Values of Dairy Cattle during Dry Period in Pangalengan: Hematology, Heart Rate, Respiration Frequency, and Body Temperature

Abstract: ABSTRAKKecamatan Pangalengan berada pada ketinggian 10001400 mdpl dengan suhu per tahun berkisar antara 1228°C dengan kelembapan per tahun 6070%. Kondisi lingkungan Pangalengan ini dapat memengaruhi kondisi fisiologis dan kesehatan sapi perah, khususnya pada saat kering kandang. Informasi tentang nilai fisiologis sapi pada saat kering kandang sampai saat ini belum tersedia. Penelitian menggunakan 46 ekor sapi perah kering kandang dan pengukuran parameter fisiologis dilakukan pada pagi, siang, dan sore hari.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A longer dry period does not cause an increase in milk production [10]. The dry period requires dairy cows to rest the udder glands and increase body deposits resulting in next milk production being improved, while the alveolar glands in the mammary glands are recovering to be ready to produce milk on the next lactation [11]. Alveolus is a place to synthesize milk elements, so the new cells and maintained cells will affect the increase or decrease the synthesized milk elements [12].…”
Section: Resultsmentioning
confidence: 99%
“…A longer dry period does not cause an increase in milk production [10]. The dry period requires dairy cows to rest the udder glands and increase body deposits resulting in next milk production being improved, while the alveolar glands in the mammary glands are recovering to be ready to produce milk on the next lactation [11]. Alveolus is a place to synthesize milk elements, so the new cells and maintained cells will affect the increase or decrease the synthesized milk elements [12].…”
Section: Resultsmentioning
confidence: 99%
“…The respiration Rate and heart rate of the calf are normal because The ranges of heart rate, and respiration rate, for dry dairy cows were 52.8-70.2 times/minute and 18.9-36.6 times/minute (Suprayogi et al, 2019). The ambient temperature at the research location during the day and evening indicated that the environment was at a critical temperature condition for dairy cows.…”
Section: Relation Of Heat Stress (Thi) With a Physiological Response ...mentioning
confidence: 96%
“…Heifers experienced a critical temperature of 22.5°C and a humidity of 78% in Bogor, namely the respiration rate of 27-38 times/minute, while in Jakarta, the critical temperature of heifers was 23.5°C and 78% humidity, namely the respiration rate of 26-46 times/minute. Respiratory rate is influenced by body size, animal age, physical activity, restlessness, ambient temperature, pregnancy, digestive system disorders, health conditions, and animal position (Suprayogi et al, 2019) and increased respiratory rate situations of stress, work, fever, and pain. There can also be a decrease in the frequency of breathing in the respiratory center sensitivity to depression in cases such as increased pressure in the brain, loss of consciousness, uremia, and increased oxygen pressure.…”
Section: Relation Of Heat Stress (Thi) With a Physiological Response ...mentioning
confidence: 99%
See 2 more Smart Citations